Economic Empowerment of Women through Information Technology: A Case Study from an Indian State - P.N. Prasad and Dr. V. Sreedevi (Journal of International Women.s Studies Vol. 8 No4 May 2007, 2007)
It is universally accepted that Information Communication Technologies (ICT) offer immense opportunities for the comprehensive social and economic development of the people all over the world. Without its adoption, there is little chance for countries or regions to develop. However, the potential of ICT as a technology for promoting micro-enterprises by poor women is still unused in many countries. This article discusses the success story of a government project for poverty eradication using ICT. The case study on ,ICT micro-enterprises by self-help group of poor women' describes the story of a self-help group, which uses potential of ICT for poverty eradication through economic empowerment of poor women. It illustrates how ICT can effectively be used as a technology for micro-enterprises, which are promoted by poor women under self-employment scheme. The article also deals with SWOT analysis that identifies the strengths, weaknesses, opportunities and threats for ICT based micro-enterprises. The article proves that if a country has the necessary enabling environment permitting the establishment of ICT micro-enterprises, poor women can promote such business for their economic empowerment